IDENTIFIKASI BANJIR IMPOR KENTANG DAN DAMPAKNYA TERHADAP HARGA DOMESTIK KENTANG DI INDONESIA - Hadiwiyono Hadiwiyono; Muhammad Firdaus; Lukytawati Anggraeni (IPB University, 2013)
Indonesia needed to be cautious of import surge since it has potential to influence import value and price in the era of trade globalization. The main purpose of this reasearch was to examine whether import surge occurred for horticulture commodities in Indonesia, especially for potato. The methods used for identifying occurrence of import surge was based on Special Safeguard Mechanism framework of World Trade Organization which will strengthened with Vector Error Correction Model to analyse the impact of import surge to domestic prices. Based on Special Safeguard Mechanism framework, volume-based Special Safeguard Mechanism triggered in almost all year during 2002-2012 but price-based Special Safeguard Mechanism is not triggered in those years. Based on Impuls Response Function analysis, the impact of import surge shock to domestic price was relatively low but occurred permanently. Based on Forecast Error Variance Decomposition analysis, import surge variables contributed slightly to the domestic price variability but it tend to increased as time. Keywords: Horticulture, Potato, Special Safeguard Mechanism, Import Surge, Vector Error Correction Model